Experimental investigation of torque measurement in hermetic compressor. (August 2019) - Xu, J; Liu, P; Ren, L P; Kong, L C
Abstract: In order to measure the compressor torque accurately and guide the design efficiently, a torque measurement method for the hermetic compressor is proposed. Then the shaft power measuring system is established by using a virtual instrument developed by LabVIEW. The stability of slip ring is monitored in real time through an external static full bridge circuit for eliminating the influence of its unstable contact resistance on measurement during the working process. The experimental results indicate that the change of contact resistance cannot be neglected in measuring process. The experimental torque curve is in agreement with the theoretical one. The measured shaft power of the prototype is 320W, finally the motor efficiency and the mechanical efficiency is 91.7% and 89.1%, respectively.